The Effect of Chronic liver diseases on homocysteine and vitamin B12 in patients serum - Al-Jumaily, Essam F.; Khaleel, Faiha’a M.; Al-Rawi, Anis (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Homocysteine (Hcy) is a sulfur containing amino acid that is formed as an intermediary in methionine metabolism. Raised plasma homocysteine levels, which may contribute to the increased risk of chronic liver disease. Patients and Methods: Sixty two patients with chronic liver disease and 26 healthy individuals were included as normal controls for the study. The HPLC system was used for the determination of Hcy and vitamin B12. Results: A highly significant Hcy concentrations were noted in all patients with cirrhosis, chronic hepatitis or liver mass. There was a trendency towards higher Hcy concentrations in more advanced stages of liver disease. The study showed that the concentrations of total Hcy were significantly higher in the patients than in the normal control group, irrespective of the age or gender. Mean serum concentration of vitamin B12 were significantly increased in cirrhotic patients and those with liver cancer compared to the control subjects and chronic hepatitis symptomatic patients. Conclusion: The serum levels of both homocystein (Hcy) and vit. B12 were significantly increased in cirrhotic patients and those with liver cancer compared to chronic hepatitis symptomatic patients.